The State and community Environmental Education in Peru - Polo Espinal, Julio Cesar (2013)
Environmental health, according to the World Organizacon of Health is "a discipline that comprises those Salud_humana aspects, including quality of life, social welfare, etc., which are Physical determined by environmental factors; chemical, biological, social and psychosocial. It also refers to the theory and practice of assessing, correcting, controlling and preventing those factors in the environment that can potentially affect adversely the health of present and future generations". This answer is critical environmental culture in a society to establish behaviors and current opinion aimed at caring for the environment associated health.